Clinical outcome of the 2nd generation cryoballoon for pulmonary vein isolation in patients with persistent atrial fibrillation — A sub-study of the randomized trial evaluating single versus dual cryoballoon applications. (1st March 2019) - Mörtsell, David; Jansson, Victoria; Malmborg, Helena; Lönnerholm, Stefan; Blomström-Lundqvist, Carina
Abstract: Aims: To assess the efficacy of the 2nd generation Cryoballoon for pulmonary vein isolation (PVI) in patients with persistent atrial fibrillation (PersAF), and to compare it to patients with paroxysmal atrial fibrillation (PAF). Methods: The outcome (arrhythmia recurrence at 12 months) was prospectively assessed in patients with PersAF( n  = 77) and compared to that in patients with PAF( n  = 62), who underwent PVI within a randomized trial evaluating single versus dual applications with the 2nd generation cryoballoon. Other endpoints included symptoms of AF, quality of life, procedure related characteristics, redo ablation rates and adverse events. Variables predicting recurrences were studied including all patients. Results: Freedom from arrhythmia recurrence was 64.9% after a single ablation and 68.8% after one or more procedures, which was significantly lower compared to PAF patients; 82.2% ( p  = 0.029) and 83.9% ( p  = 0.048) respectively, at 12 months. The improvements in EHRA score (−1.3 ± 0.8, p  < 0.0001), symptom severity score (SSQ) (−5.0 ± 4.2, p  < 0.0001) and EQ5D-5 L global score (+10.4 ± 20.3, p  = 0.0002) after ablation was significant compared to baseline. The re-ablation rate was 7/77 (9.1%) which did not differ from that in PAF patients, 9/62 (14.5%), p  = 0.42. Procedure duration, 104.8 ± 37.4 versus 113 ± 31.2 min ( p  = 0.129), application time, 1605 ± 659 versus 1521 ± 557 s ( p  = 0.103) and total adverse events after 12 months, 8/77 (10.4%) versus 5/62 (8.1%) ( p  = 0.77) did not differ in PersAF versus PAF patients. Conclusion: Both symptoms and QoL improved significantly in patients with PersAF after ablation. Freedom from AF was clinically significant but lower than in PAF patients. The cryoballoon seems an effective technique also in patients with persistent AF. Highlights: Symptoms and QoL improved in persistent AF and did not differ from paroxysmal AF patients after cryoballoon ablation Freedom from AF 12 months after a single ablation was clinically significant at 64.9%, but lower than in paroxysmal AF Cryoballoon ablation seems to be a feasible and effective technique in persistent AF